Neuroinflammation imposes vulnerability to tau propagation: The role of microglia activation in the development of amyloid and tau pathology in Alzheimer's disease. (7th December 2020) - Rosa‐Neto, Pedro; Pascoal, Tharick A.; Benedet, Andréa Lessa; Kang, Min Su; Savard, Melissa; Mathotaarachchi, Sulantha; Edison, Paul; Chamoun, Mira; Stevenson, Jenna; Therriault, Joseph; Massarweh, Gassan; Soucy, Jean‐Paul; et al.
Abstract: Background: Translocator protein (TSPO) is an 18 kDa protein has been considered a target for neuroinflammation. Using multiparametric acquisitions, we tested in a large‐scale cohort the hypothetical framework proposing that neuroinflammation imposes vulnerability to neurofibrillary tangles (NFT) formation and propagation. Methods: We studied cognitive unimpaired and impaired individuals from the Translational Biomarkers in Aging and Dementia (TRIAD) cohort who had a complete baseline clinical and cognitive assessments, structural MRIs, [ 11 C]PBR28, [ 18 F]MK6240 and [ 18 F]AZD4694 (PET proxies for TSPO, NFT and Αβ, respectively). The PET outcome measure was the SUVR. A fraction of these individuals also had CSF cytokines analysed using the Olink Platform. We conducted ROI path analysis and voxel‐based analysis to establish the associations between [ 11 C]PBR28, [ 18 F]MK6240 and [ 18 F]AZD4694. Results: A total of 138 (CN=90; MCI=30=; AD=18) individuals were included in this analysis. We found that brain [ 11 C]PBR28 uptake was correlated with CSF biomarkers of neuroinflammation. We also found an age‐related increase of [ 11 C]PBR28 uptake. [ 11 C]PBR28 was increased brain in AD related areas across the its clinical spectrum. [ 11 C]PBR28 was associated with cognitive deficits in these individuals. In regards to tau aggregates, we found that [ 18 F]MK6240 uptake in the mesial temporal structures derives from local interactions between [ 18 F]AZD4694 and [ 11 C]PBR28. Importantly, path analysis revealed that [ 11 C]PBR28 and [ 18 F]AZD4694 uptake potentiated the propagation of [ 18 F]MK6240 from early to late Braak stages (Figure 1). Conclusions: Our results reveal that TSPO upregulation is part of the repertoire of biomarker alterations in patients within the entire AD clinical spectrum. TSPO is critical for the early and late tangle formation on medial temporal structures as well in advanced Braak stages. Neuroinflammation imaging agents such as [ 11 C]PBR28 provide critical information regarding inflammatory tissue responses amenable of pharmacological interventions.